Results of a Prospective Study Concerning the Clinical Efficiency of Recent Russian-Made Specialized Foods without Phenylalanine - T. V. Bushueva; T. E. Borovik; K. S. Ladodo; L. M. Kuzenkova (Педиатрическая фармакология, 2016)
Background: Specialized foods, based on aminoacids without phenilalanin, are the main source of protein for patients with phenilketonuria of all ages. Based on modern technologies, new Russian-made foods were created. They have an optimized aminoacid and micronutrient composition, which increases their bioavailability.Objective: Our aim was to investigate the clinical efficiency of the new Russian-made specialized foods based on aminoacids without phenylalanine, in patients with phenylketonuria.Methods: Evaluating physical, somatic and neuropsychic development as well as measuring phenylalanine blood level were carried out twice: before the prescription and after 1 month of using the new Russian-made specialized foods. The chemical composition of the ration was controlled using dietology methods.Results: 57 children at the age of 14 days to 15 years with phenylketonuria (which was detected in neonatal screening) were picked for this study. A hypophenylalanine diet has been prescribed for all children no later than at the age of 3 months of life. In children of the first year (I group) (among which there were children with high phenylalanine blood levels) phenylalanine concentration decreased from 5,5 (4,0; 21,0) to 4,4 (3,7; 4,7) mg/dl (p = 0,014) while using Russian-made specialized foods. In this group of children the psychomotor and physical indices improved. In early childhood-, preschool- and school-aged patients phenylalanine blood level remained steady. The chemical composition of the ration with Russian-made foods, based on aminoacids without phenylalanine, corresponded to the reference intake of main nutrients and energy.Conclusion: Hypophenylalanine diet with new Russian-made specialized foods without phenylalanine (which is designed for phenylketonuria patients of various age groups) showed high clinical efficiency of these foods.